2020
DOI: 10.1111/eip.12947
|View full text |Cite
|
Sign up to set email alerts
|

Horyzons USA: A moderated online social intervention for first episode psychosis

Abstract: Aim We evaluated the feasibility and acceptability of Horyzons, an online social media platform designed to facilitate relationship development among, and introduce therapeutic content to, first‐episode psychosis (FEP) clients. We also evaluated whether participation in the platform was related to reduced loneliness, improved social integration and increased psychological well‐being. Methods Twenty‐six participants diagnosed with a schizophrenia spectrum disorder were provided access to the moderated Horyzons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Feedback offered insights into attitudes toward the innovation, potential barriers to its implementation, and adaptations to make before piloting the intervention within a Canadian context. Some of the suggestions from participants in this study are consistent with those reported in previous research on Horyzons (eg, making the intervention accessible via mobile devices) [ 11 ]; concurrently, many of the suggestions for adaptations and improvement are novel. This may be due to the qualitative nature of our process, the elicitation of feedback from multiple stakeholder groups (ie, clinicians in addition to patients), the multiple opportunities given to reflect and contribute, the active engagement of participants in the adaptation process, and the factors related to context (eg, different characteristics of the employment and health sector).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Feedback offered insights into attitudes toward the innovation, potential barriers to its implementation, and adaptations to make before piloting the intervention within a Canadian context. Some of the suggestions from participants in this study are consistent with those reported in previous research on Horyzons (eg, making the intervention accessible via mobile devices) [ 11 ]; concurrently, many of the suggestions for adaptations and improvement are novel. This may be due to the qualitative nature of our process, the elicitation of feedback from multiple stakeholder groups (ie, clinicians in addition to patients), the multiple opportunities given to reflect and contribute, the active engagement of participants in the adaptation process, and the factors related to context (eg, different characteristics of the employment and health sector).…”
Section: Discussionsupporting
confidence: 79%
“…Horyzons has been tested on a sample of 20 young Australian adults for its feasibility, acceptability, utility, and safety [ 9 , 10 ], and more recently, it has been pilot-tested in other international contexts [ 11 ]. There is also a randomized controlled trial of Horyzons [ 12 ] that was completed in 2018 and is currently undergoing data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Horyzons has now been adapted and successfully piloted in specialized FEP services in the US 46 and Canada 47 , with clinical implementation efforts underway in both countries as well as Australia. Ultimately, with specialized FEP services now being available across the US, Canada, Europe, Asia and Australasia, Horyzons holds significant promise as a novel, engaging and sustainable intervention to improve vocational recovery, reduce utilization of emergency services and provide continuous support for young people with FEP beyond specialized care.…”
Section: Discussionmentioning
confidence: 99%
“…An online social media platform for people with early psychosis, known as MOST, works to promote relationship development and present therapeutic information to this population. This platform was tested on first‐episode psychosis patients and was found to be feasible, effective, and well‐received (Ludwig et al, 2020). In response to the growing potential of technology implementation into care, the National Institute of Mental Health commissioned a report to assess the current state and technology readiness of CSC in the summer of 2019.…”
Section: Introductionmentioning
confidence: 99%